PSYCHOLOGICAL FACTORS AFFECTING ENGLISH SPEAKING PERFORMANCE AT ELEVENTH GRADE STUDENTS’ IN SMK AL-INAYAH TEBO - Pratiwi, Ria Indah; Andriani, Reni (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
This research is about students who have some problems in speaking English. This research was conducted at the Vocational High School Al-inayah Tebo. The purpose of this study was to determine the factors that influence students’ difficulties in learning English skills. The design of this research used qualitative descriptive method. The subjects of this research were students and teachers of eleventh grade at the Vocational High School Al-inayah Tebo. The research data were collected using observation and interviews. The result showed that students experienced several problems that were influenced by their psychological factors in speaking English, such as : Lack of motivation, Anxiety, Lack of confidence, Shyness, Fear of making mistake, Learning environment Factors, Performance condition factors. From these problems, the most dominant factor was fear of making mistakes. Most of the students stated that they were afraid to speak because they could not pronounce it. Most of them are afraid if they make mistake so they better not speak English.